Placental pathology in women with HIV. (November 2021) - Ikumi, Nadia M.; Matjila, Mushi; Gray, Clive M.; Anumba, Dilly; Pillay, Komala
Abstract: Recognizing the importance of placental features and their unique functions can provide insight into maternal health, the uterine environment during the course of pregnancy, birth outcomes and neonatal health. In the context of HIV and antiretroviral therapy (ART), there have been great strides in the prevention of mother to child transmission of HIV. However, there is still paucity of data on the impact of HIV/ART exposure on placental pathology and studies available only examine specific patterns of placental injury, further justifying the need for a more defined and comprehensive approach to the differential diagnoses of HIV/ART-exposed placentae. The purpose of this review is to consolidate findings from individual studies that have been reported on patterns of placental injury in the context of HIV/ART exposure. In both the pre- and post-ART eras HIV and/or ART has been associated with placental injury including maternal vascular malperfusion as well as acute and chronic inflammation. These patterns of injury are further associated with adverse birth outcomes including preterm birth and current evidence suggests an association between poor placental function and compromised fetal development. With the ever increasing number of pregnant women with HIV on ART, there is a compelling need for full incorporation of placental diagnoses into obstetric disease classification. It is also important to take into account key elements of maternal clinical history. Lastly, there is a need to standardize the reporting of placental pathology in order to glean additional insight into the elucidation of HIV/ART associated placental injury. Highlights: Antiretroviral therapy (ART) has clear benefits for both the mother and infant however these do not come without risks. The risk of maternal vascular malperfusion may be twice as high in women who initiated ART before pregnancy. Acute chorioamnionitis is the most widely reported histopathological diagnosis in placentae of pregnant women with HIV. Villitis of unknown etiology and chronic deciduitis have been variably reported in pregnant women with HIV. There is a gap in evidence associating placental features with clinical history, outcomes and infant follow-up.